The Role of Local Government in Improving the Regional Economy Through the Tourism Sector - Tedyansyah, Tedyansyah; Saputro, Guntur Eko; Suwito, Suwito (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
The local government regulated environment will be affected by tourism governance. The development of poorly managed tourist facilities and the impact of tourism on important historical places that need to be preserved are issues in tourism governance. The economic benefits of tourism are often higher than the benefits to local communities. The approach used by the researchers was a literature review, which involved tracing literature sources including books, papers, scientific journals, and other print and online materials related to the topic under study. The development of the tourism sector in Indonesia has a great opportunity to strengthen the economy in the region where the tourism sector is located. The Indonesian government is improving the tourism sector by improving infrastructure, promoting tourism, and improving human resources. Through growth and good management, tourism can help the Indonesian economy by increasing regional income.